Precocious and Problematic?The Consequences of Youth Violent Victimization for Adolescent Sexual Behavior - Warner, Tara D. (Journal of developmental and life-course criminology, 2019)
Violent victimization is concentrated in adolescence and is disruptive to both the timing and sequencing of key life course transitions that occur during this developmental stage. Drawing on recent work establishing the interpersonal consequences of youth victimization, we examined the effect of violent victimization on adolescents’ timing of sexual debut and involvement in additional sexual risk behaviors (multiple sexual partnering and inconsistent contraceptive use).